2010
DOI: 10.4028/www.scientific.net/amr.168-170.351
|View full text |Cite
|
Sign up to set email alerts
|

The Performance Analysis of Semi-Flexible Pavement by the Volume Parameter of Matrix Asphalt Mixture

Abstract: The volume parameter of matrix asphalt mixture is an important target in the design of the semi-flexible pavement. The research used volume-standar to design four kinds of matrix asphalt mixture, fulfilled mechanics performances and performances of semi-flexible pavement material with different aging, compared with common asphalt mixture and researched the effect by air void and pore structure. It proves that the compacted intensity, high-temperature stability and low temperature bend of the semi-flexible pave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…The slurry has high fluidity and is able to penetrate the voids in the open-graded asphalt mix. The fast curing cement slurry locks the asphalt mix in a fixed structure, which is resistant to deformation, abrasion and attack by fuel and chemicals (Ding et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The slurry has high fluidity and is able to penetrate the voids in the open-graded asphalt mix. The fast curing cement slurry locks the asphalt mix in a fixed structure, which is resistant to deformation, abrasion and attack by fuel and chemicals (Ding et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Pei et al [6,7] determined that the cement slurry was more suitable as a grouting material by comparing the fluidity, strength and drying shrinkage of cement slurry and cement mortar, and then pouring the two grouting materials into the asphalt mixture for performance evaluation. Ding et al [8] analyzed the performance of semi-flexible pavement in the volume parameters of matrix asphalt mixture, and found that the high-low temperature stability of semi-flexible pavement materials was superior to ordinary asphalt pavement materials, and the performance of the matrix asphalt mixture with more air voids was better. At the same time, some scholars improved the performance of grouting materials by using additives.…”
Section: Introductionmentioning
confidence: 99%
“…Semi-flexible pavement (SFP) material is a kind of pavement material which is composed of a special cement mortar infused in the large voids of an open-graded matrix asphalt mixture [1,2]. Its high temperature stability is better than that of asphalt pavement, and it has superior deformation resistance, water damage resistance, and skid resistance.…”
Section: Introductionmentioning
confidence: 99%